2019
DOI: 10.1029/2018jb016822
|View full text |Cite
|
Sign up to set email alerts
|

CH4and CO2Emissions From Mud Volcanoes on the Southern Margin of the Junggar Basin, NW China: Origin, Output, and Relation to Regional Tectonics

Abstract: The concentrations, isotope ratios, and fluxes of CH 4 and CO 2 from mud volcanoes measured during a field survey on the southern margin of the Junggar Basin are reported. The origins and outputs of CH 4 and CO 2 from the four mud volcanoes are assessed, and the relationship between the characteristics of degassing and regional tectonics is discussed. The geochemical data indicate that thermogenic gases derived from the hydrocarbon reservoirs beneath anticlines could be the main source of the CH 4 emitted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(62 reference statements)
1
6
0
1
Order By: Relevance
“…In the petroliferous basins considered herein, the leakage of CH 4 and CO 2 will be larger when an earthquake occurs than during normal times (Cui Y et al, 2017). In the active fault of the basin's edge, the leakage of CH 4 and CO 2 is consistent with the intensity of regional tectonic activity (Chen Z et al, 2019a, b).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In the petroliferous basins considered herein, the leakage of CH 4 and CO 2 will be larger when an earthquake occurs than during normal times (Cui Y et al, 2017). In the active fault of the basin's edge, the leakage of CH 4 and CO 2 is consistent with the intensity of regional tectonic activity (Chen Z et al, 2019a, b).…”
Section: Resultssupporting
confidence: 60%
“…They also suggested that the warming effect might be related to seismogenic mechanisms; however, this is relevant only if the geological conditions and basin topography allow the gases to gather, which results in the gases being released to form a CTIB anomaly. Besides, with the absence of greenhouse gases escaping in the Junggar basin's faults and the west Sichuan basin (Cui Y et al, 2017; Chen Z et al, 2019a, b), fewer gases are escaping before EQs in other basins if these basins are without gas reservoirs.…”
Section: Resultsmentioning
confidence: 99%
“…图 1(彩) 准噶尔盆地区域断裂控制了 CO 2 与 CH 4 的释放模型图 [26] Figure 1 The modal of regional faults in the Junggar Basin control the release of CO 2 and CH 4 [26] 在区域尺度,流体的释放也受局部断裂构造的控制。加纳东南部断裂发育地区的土壤气 Rn 浓度最高可达 115 kBq/m 3 ,而在周边没有断层的地区则低于 20 kBq/m 3 [25] ;对准噶尔盆地南缘泥 火山研究发现,区域断裂控制了 CO 2 和 CH 4 的释放,且四个背斜褶皱的输出通量分布与区域构 造活动强度非常一致 [26] (图 1);中国大陆活动构造发育的南北地震带、张家口-渤海湾(张渤)地震 带、北天山地震带等也均是重要的脱气带(表 1),且气体释放强度与断裂活动程度密切相关 [55] ; 在具备更丰富气体运移通道的断裂带交汇部位,气体浓度值往往也更高 [56] . 在水热活动区,大气 降水及地表水通过活动断裂(可至地幔)进行深部循环,通过混合、溶解、解析、水岩反应等过 程,不断地将深部信息携带至近地表,成为解译深部动力学过程的特殊密码.…”
Section: 流体地球化学与构造活动关系 地下流体在浓度差和温度、 压力变化的驱动下沿着活动断裂等薄弱地带在岩石圈内发生扩散、unclassified
“…The active fault system, along with its associated fractures at the block boundary, plays a fundamental role in serving as the preferred pathway for the propagation of deep gas (Caracausi & Sulli, 2019; Sano et al., 2017; Xu et al., 2017; Zheng et al., 2017). Through rock loading experiments, it has been determined that amplified radon (Rn) emissions from broken rocks can be attributed to the increased presence of fractures (Chen et al., 2019; Toutain et al., 1992; Tuccimei et al., 2010). Field measurements and monitoring have further demonstrated that the spatial and temporal variations of soil gas Rn concentrations and fluxes in active fault zones are closely linked to fault activity (Fu et al., 2017; Wang et al., 2014; Yang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%